CONTINUOUS HORIZONTAL CASTING INTO JET CRYSTALLIZER OF INGOTS WITH DIAMETER 70 MM OF SILUMIN AK 18 - V. Ju. Stetsenko; A. I. Rivkin; A. P. Gutev; A. M. Pevnev; R. V. Konovalov; Suk-Bong Kang (Литьë и металлургия)
It is shown that continuous horizontal casting of hypereutectic silumin Al+18%Si in jet crystallizer allows to obtain ingots of 70 mm in diameter with modified eutectic, and use of method of hereditary modification provides crushing  f crystals of primary silicon without application of admixture modifiers.